Functionalized Carbon Nanotube Sensors for the Detection of Sub-ppm Nitric Oxide Gas - Kang, Byeong-Cheol; Jeon, Jun-Young; Byun, Young Tae; Ha, Tae-Jun (AMER SCIENTIFIC PUBLISHERS, 2018)
In this paper, we demonstrate the highly sensitive carbon nanotube (CNT) sensors for the detection of sub-ppm nitric oxide (NO) gas operating at room temperature. Such achievement can be realized by functionalizing CNT thin films with amine-based polymers through a solution-process technology at low temperature. In addition to high sensitivity, functionalized CNT sensors exhibit high selectivity towards NO gas, which is an effective and practical factor for health-care monitoring nano-electronics. We also investigated the effect of a post-cleaning treatment on the sensing performance of functionalized CNT thin films for sub-ppm NO gas sensors. We believe that this work can open-up new routes to realize high performance human-interactive electronics for respiratory diseases detection in exhaled air.
Keywords: SENSING PROPERTIES